Improvement of Change Over Time of Cage Press Machine in Bearing Production at PT. XYZ Using the SMED Method - Riri Nur Fadilah; Siti Rahayu; Fibi Eko Putra (Universitas Islam Raden Rahmat, Malang, 2025)
PT. XYZ is a manufacturing company with its production, namely bearings, both from small to large sizes. The growth of bearing sales interest is increasing every year, therefore PT XYZ must be able to adjust to the needs of consumers. This causes many types of bearings that must be produced by PT XYZ, this type change affects the time in the machine change over process. This research was carried out with the aim of reducing the time used for the machine change over process, especially on the chage press machine which has been seen through patchwok data. The improvements made are by using the PDCA and SMED methods, to be able to find out what factors are the cause of the long change over and also how to reduce the time in the change over process of the machine, With the implementation of SMED PT. XYZ managed to reduce the time from 1 hour 9 minutes 56 seconds to 9 minutes 1 second with a time reduction of 1 hour 55 seconds or equivalent to 87.85%. Thus, this SMED method can be used to improve engine change time to make it faster.